1991
DOI: 10.1017/s0003356100013076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy intake on protein and energy metabolism of boars of high genetic potential for lean growth

Abstract: Two experiments were conducted each using one batch of six Landrace littermate, entire male, pedigree pigs in a Latin-square change-over study of the effects of energy intake on nitrogen and energy metabolism over the range 33 to 88 kg live weight. One animal from each litter was slaughtered at 33 kg body weight to obtain initial body composition data. Five feeding levels (80, 100, 120, 140 and 160g/kg M0·63) were used during five consecutive metabolism trials each of 11-days duration, excreta being collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 15 publications
3
16
0
Order By: Relevance
“…The low marginal efficiency of PD at restricted intakes (1.34 g PD per MJ increase in ME intake) is associated with the low PD max found in the Iberian pig at this stage of growth. This observation confirms the suggestion that the decrease in PD due to restriction in energy allowance would be greater in pigs of higher genetic potential for lean tissue deposition (Campbell and Taverner, 1988;Rao and McCracken, 1991;Quiniou et al, 1996). In Iberian pigs growing from 15 to 50 kg BW, Nieto et al (2002) reported a marginal efficiency for PD of 2.81 g PD per MJ ME with the diet that provided the optimal protein concentration for growth.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The low marginal efficiency of PD at restricted intakes (1.34 g PD per MJ increase in ME intake) is associated with the low PD max found in the Iberian pig at this stage of growth. This observation confirms the suggestion that the decrease in PD due to restriction in energy allowance would be greater in pigs of higher genetic potential for lean tissue deposition (Campbell and Taverner, 1988;Rao and McCracken, 1991;Quiniou et al, 1996). In Iberian pigs growing from 15 to 50 kg BW, Nieto et al (2002) reported a marginal efficiency for PD of 2.81 g PD per MJ ME with the diet that provided the optimal protein concentration for growth.…”
Section: Discussionsupporting
confidence: 82%
“…Noblet et al (1999) and Van Milgen and Noblet (1999) concluded that body muscle and, even more importantly, visceral mass explain a large part in the variation of ME m . Higher maintenance energy requirements in lean genotypes are supported by the findings of Thorbek et al (1984), Campbell and Taverner (1988) and Rao and McCracken (1991).…”
Section: Discussionmentioning
confidence: 57%
“…Part of this information derives from studies made with modern strains of pigs of high genetic potential. For these animals, energy intake seems to be a limiting dietary factor and, in the young animal, the major constraint on growth (Close et al 1979;Campbell & Dunkin, 1983a,b;Rao & McCracken, 1991. The results suggest that the selection has raised the genetic capacity of these pigs for lean gain beyond the upper limit of appetite.…”
Section: Discussionmentioning
confidence: 98%
“…Expressing amino acid requirements as a ratio to energy ensures that adequate amino acids are consumed, appropriate to the animal's growth, irrespective of changing dietary energy concentration (Smith et al 1999). In addition, the relationship between energy intake and protein deposition is assumed to be linear in pigs weighing less than 90 kg (Campbell and Taverner 1988;Rao and McCracken 1991;Bikker 1994). It is therefore essential that lysine requirements for this category of pig be expressed in relation to dietary energy concentration (Nam and Aherne 1994;Van Lunen and Cole 1998).…”
mentioning
confidence: 99%